(untitled) (Journal of Plant Disease Sciences, 2017)
Twenty strains of (AF-1 to AF-20) were isolated from Aspergillus flavus the seeds of twenty different samples of groundnut. Studies on the cultural, morphological and aflatoxigenic variability was done for all the isolates Isolates . AF-9 and AF-18 belonged to the fast growing category (>50 mm colony diameter) whereas; AF-5, AF-11, AF-16, AF-17 and AF-20 belonged to the slow growing category (<35 mm colony diameter). The colour of the outer surface of the mycelium ranged from creamy white to dull white and fluffy to flat. Dry mycelial weight was recorded maximum in AF-18 (576.25 mg) and the least in the isolate AF-20 (243.51 mg). Highest sporulation was recorded in AF-11(32.85 x 10 spores 6 ml ) and least sporulation in isolate AF-5 (3.75 x 10 spores ml ). Potato dextrose -1 6 -1 agar medium was found most suitable for aflatoxigenicity test followed by the Czapek’s Dox agar medium. The aflatoxigenicity test showed AF-8 to be highly toxigenic while seven isolates (AF-1, AF-9, AF-10, AF-11, AF-15, AF-17, and AF 20) were non-toxigenic.